Thermal Conditioning Can Improve Thermoregulation of Young Chicks During Exposure to Low Temperatures - Ouchi, Yoshimitsu; Chowdhury, Vishwajit S.; Cockrem, John F.; Bungo, Takashi (Frontiers in Animal Science, 2022)
The risk of climate change is increasing year by year and changing environmental temperatures will increasingly have effects on productivity in the poultry industry. Thermal conditioning is a method of improving thermotolerance and productivity in chickens that experience high ambient temperatures. Thermal conditioning involves exposure of chickens to high temperatures at an early age. This conditioning treatment can affect tolerance to other type of stress. However, the effect of thermal conditioning on tolerance of low temperatures has not been investigated. Therefore, in this study we investigated the effect of thermal conditioning in chickens on thermoregulation during exposure to low temperatures. 3 day-old female broiler chicks were exposed to high ambient temperatures (40°C for 12 h) as a thermal conditioning treatment. A control group of chicks was kept at 30°C. At 7 days-old, both groups of chicks were exposed to low temperatures (16 ± 0.5°C) for 3 h. Thermal conditioning treatment reduced the decrease in rectal temperature during cold exposure that occurred in control chicks. In addition, hypothalamic mRNA expression of brain derived neurotrophic factor, thyrotropin-releasing hormone and arginine vasotocin genes was higher in thermal conditioning treated chicks than control chicks. The mRNA expression of avian uncoupling protein in the liver was also higher in thermal conditioning chicks. These results suggest that thermal conditioning treatment can improve thermoregulatory mechanisms of chicks under low temperature environments.